EMPOWERING WOMEN THROUGH MAKING SNACKS TO INCREASE FAMILY INCOME (STUDY ON THE MOTEKAR I SMALL FARMER GROUP (KPK) IN WATES, GODOG VILLAGE, KARANGPAWITAN DISTRICT, GARUT REGENCY) - Khairul Azmi; Asep Saepudin; Iip Saripah (Jurnal Scientia, 2023)
This study aims to find out how to empower women to increase family income through the Motekar I Small Farmers Group. Motekar I Small Farmers in empowering women to increase family income made the program an empowerment for the community . Efforts to increase community independence in fulfilling needs through groups and small entrepreneurs make a product. The theory used in this study is women's empowerment, family economy, social organizing, agricultural processing, creating an entrepreneur. This research method uses qualitative methods. This data collection technique was seen from observational studies, documentation and interviews. Data analysis techniques in the stages of data collection, data reduction, data presentation and conclusions. The results of research on women's empowerment to increase family income for members of the Motekar I KPK to develop their potential in accordance with the identification of community needs needs development so that they can progress, empowerment is the key to solving problems for families and women. Women's empowerment programs through making snacks are the motor or driving force in creating or increasing income, especially for women. The distribution of snacks which was held at the KPK Motekar I became an innovation for women and became a vehicle for creating an entrepreneur and an alternative to family problems.